Investigating popular topics for the integration of the internet of things in physical education: A content analysis in higher education - Quintero, Armando Monterrosa; Valderrama, Felipe Poblete; Quiroga, Sergio Ricardo (UIR Press, 2024)
Background Problems: Advanced technologies, such as the Internet of Things (IoT), have played an increasingly important role in the development of physical education in higher education. Research Objectives: This study aims to conduct a content analysis of the use of IoT technology in physical education in higher education. Methods: Scopus and Web of Science databases were used to collect and analyse data for this study, with a total of 178 articles obtained, consisting of 104 articles (Scopus) and 74 articles (Web of Science). The final data used for this study consisted of 20 articles, as it only targeted the top five topics related to the internet of things (IoT) in physical education after being analysed using ScientoPy. Findings and Results: The analysis identified five main topics related to the application of the internet of things in physical education in higher education, including cloud, artificial intelligence, deep learning, big data, and virtual reality. The implications of these findings for the development of physical education in higher education are discussed in this study, emphasizing the importance of IoT technology integration in creating a more adaptive and responsive learning environment. Conclusion: The contributions of this research include providing deeper insights into how IoT technologies can be applied in physical education in higher education, as well as highlighting the potential to improve the effectiveness of learning and teaching in this area. The conclusions of this study emphasises the importance of continuing to develop innovations in the application of IoT technology in physical education in higher education in order to achieve a more efficient and competitive learning environment.